SIFAT SENSORY DAN FUNGSIONAL BERAS ANALOG DARI CAMPURAN ONGGOK TERFERMENTASI DAN KETAN HITAM - Siti Nurdjanah; Fibra Nurainy; Redy Destian Revialdy (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
There are a lot variety of products can be used for rice substitute as a staple food. One of them is analog rice processed from onggok (solid waste from tapioca production) formulated mixed with black waxy rice (BWR).  Onggok has poor quality when applied on food products, therefore  natural fermentation and addition of BWR can be used as an alternative to improve it. The objective of this research was to find out the proportion of  onggok and BWR in  producing analog rice that has the best organoleptic and contains functional food. This research was conducted within a complete randomized block design with a single factor and four replications. The single factor was the formulation of onggok and BWR consisted of 6 levels: 100:0 (F0), 90:10 (F1), 80:20 (F2), 70:30 (F3), 60:40 (F4), 50:50 (F5)  The results showed that the best formulation was found on F3 (70% onggok and 30% BWR). The best analog rice had the characteristics of purple, a mild BWR  aroma, and  slightly  liked in overall acceptance of raw sample. The cooked rice had the characteristics of black-purple in color, mild BWR  in aroma, slightly chewy in texture,  mild BWR in taste, and slightly liked in overall acceptance. The  moisture, ash, lipid, protein and carbohydrate contents were 3.0%, 0.9%, 1.4%, 6.2%, and 86.3% . The conversion of rice to glucose as hidrolyzed using α amylase was 12.4%, and total phenolic content was 14,5 mg/g. Keywords: analog rice, black  waxy rice, onggok, total phenolic